Balance and visual reliance in post-COVID syndrome patients assessed with a robotic system: a multi-sensory integration deficit - Gervasoni, Fabrizio; LoMauro, Antonella; Ricci, Vincenzo; Salce, Gregorio; Andreoli, Arnaldo; Visconti, Alessandro; Pantoni, Leonardo (Neurological sciences, 2022)
The symptoms of SARS-CoV-2 infection are not limited to the acute phase, with vertigo, peripheral neuropathies, headache, fatigue, memory loss, and depression being the most common post-acute clinical manifestations. Such post-COVID syndrome is a new clinically relevant challenge for diagnosis and therapy. Our goal was to quantify deficit in balance and proprioception related to post-COVID syndrome and, in this sense, we prospectively analyzed data of 66 post-COVID-19 outpatients (mean age 47.3 ± 11.1 years, 50 females, 25 hospitalized), evaluated using the robotic device hunova. The dynamic balance was assessed with open (OE) and closed eyes (CE) and three indexes, proportional to subject instability, were measured: the sway path and two oscillation ranges. Hospitalized group showed the worst performance with respect to non-hospitalized patients and normality range in both visual conditions for the sway path and the oscillation ranges, with the worst performance being with CE. When compared to normality ranges, post-COVID patients were significantly more distant from normality in the OE condition compared to the CE condition. These results suggest that independently from the severity of the disease experienced, post-COVID syndrome makes the elastic balance test performances more distant from the normality when the subject integrates vision, somatosensory information, and vestibular information. In the absence of visual feedback, patients seem to implement compensatory strategies, presumably seeking more significant feedback from the lower limbs, which improve their performance. These data suggest a new mechanism of the post-COVID syndrome that deserves further investigation for its potential impact on activities of daily living.